On the temperature measurement from the O IV emission lines - Dwivedi B.N.; Gupta A.K. (My University, 2025)
The new calculations of the O iv temperature-sensitive EUV line ratios are presented and compared with previous results. © 1994 Kluwer Academic Publishers.